2004
DOI: 10.1590/s1519-566x2004000600006
|View full text |Cite
|
Sign up to set email alerts
|

Comunidades de machos de abelhas Euglossina (Hymenoptera: Apidae) em fragmentos florestais no Sul do Brasil

Abstract: -The aim of this work was to study communities of euglossine bees in three fragments of semideciduous forest with different sizes (8.5 ha, 86 ha and 2280 ha), in Northern Paraná State (Brazil). From November 2001 through April 2002 males of euglossine bees were sampled using chemical baits. A total of 245 males from four genera and seven species visited the baits. In the largest fragment were sampled 152 males of 6 species, in the medium, 45 males of five species and, in the smallest, 48 males of seven species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
76
1
19

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 14 publications
22
76
1
19
Order By: Relevance
“…The species richness in Brejão was similar to those found in other inventories carried out in the Cerrado domain (Aguilar 1990, Rebêlo & Cabral 1997, Alvarenga et al 2007, Nemésio & Faria 2004) and in fragments of the semideciduous "low mountain rain forest" (Rizzini 1979), at elevations of 300-900 m, in the Atlantic Forest domain in the states of Minas Gerais (Nemésio 2003, Nemésio & Silveira 2007a, 2010, São Paulo (Rebêlo & Garófalo 1997) and Paraná (Sofia & Suzuki 2004). These forests are characterized by relatively open canopy, 15-25 m tall, and occur under climates with two well defined seasons, rainy and dry.…”
Section: Species Richness and Compositionsupporting
confidence: 84%
“…The species richness in Brejão was similar to those found in other inventories carried out in the Cerrado domain (Aguilar 1990, Rebêlo & Cabral 1997, Alvarenga et al 2007, Nemésio & Faria 2004) and in fragments of the semideciduous "low mountain rain forest" (Rizzini 1979), at elevations of 300-900 m, in the Atlantic Forest domain in the states of Minas Gerais (Nemésio 2003, Nemésio & Silveira 2007a, 2010, São Paulo (Rebêlo & Garófalo 1997) and Paraná (Sofia & Suzuki 2004). These forests are characterized by relatively open canopy, 15-25 m tall, and occur under climates with two well defined seasons, rainy and dry.…”
Section: Species Richness and Compositionsupporting
confidence: 84%
“…Talvez fatores como o tamanho das três áreas, a influência da vegetação do entorno (CARVALHO et al, 2006) e o isolamento da mata mesofítica quando comparada às outras áreas, possa ser considerado, entretanto são necessários estudos e testes mais quantitativos. Em diversos trabalhos realizados (BRAGA, 1976;RAW, 1989;MORATO et al, 1992;NEVES & VIANA, 1997;REBÊLO & CABRAL, 1997;REBÊLO & GARÓFALO, 1997;ALBUQUERQUE et al, 2001;SOFIA & SUZUKI, 2004;CARVALHO et al, 2006) Euglossa cordata (Linnaeus, (MORATO et al, 1992;MORATO, 1994) e na Bahia (NEVES & VIANA, 1997) onde salicilato foi bastante atrativo e em Viçosa, Minas Gerais (PERUQUETTI et al, 1999), em que vanilina foi o composto que atraiu o maior número de espécimes.…”
Section: Discussionunclassified
“…Some euglossine species are apparently sensitive to environmental disturbances (Powell and Powell 1987;Tonhasca et al 2002;Giangarelli et al 2009;Nemésio 2013), such as forest fragmentation and reduction in fragment size (Powell and Powell 1987;Sofia and Suzuki 2004;Giangarelli et al 2009). Apart from reductions in the abundance of orchid bees in forest fragments of reduced size, studies have shown that some species may have stronger dispersal limitations in fragmented landscapes, and the type of matrix may also affect the dispersal of some species of the group differently (Powell and Powell 1987;Milet-Pinheiro and Schlindwein 2005).…”
Section: Introductionmentioning
confidence: 99%